Synchronization patterns reveal neuronal coding of working memory content - Mamashli, Fahimeh; Khan, Sheraz; Hämäläinen, Matti; Jas, Mainak; Raij, Tommi; Stufflebeam, Steven M.; Nummenmaa, Aapo; Ahveninen, Jyrki (Cell reports (Cambridge), 2021)
Neuronal oscillations are suggested to play an important role in auditory working memory (WM), but their contribution to content-specific representations has remained unclear. Here, we measure magnetoencephalography during a retro-cueing task with parametric ripple-sound stimuli, which are spectrotemporally similar to speech but resist non-auditory memory strategies. Using machine learning analyses, with rigorous between-subject cross-validation and non-parametric permutation testing, we show that memorized sound content is strongly represented in phase-synchronization patterns between subregions of auditory and frontoparietal cortices. These phase-synchronization patterns predict the memorized sound content steadily across the studied maintenance period. In addition to connectivity-based representations, there are indices of more local, “activity silent” representations in auditory cortices, where the decoding accuracy of WM content significantly increases after task-irrelevant “impulse stimuli.” Our results demonstrate that synchronization patterns across auditory sensory and association areas orchestrate neuronal coding of auditory WM content. This connectivity-based coding scheme could also extend beyond the auditory domain. [Display omitted] •How neurons in human brain store transient working memories (WMs) is debated•We hypothesize that interregional phase synchronization supports WM maintenance•We decode auditory memories from magnetoencephalograms to test this hypothesis•Synchronization patterns across sensory and higher areas reveal content held in WM Mamashli et al. use machine learning analyses of human magnetoencephalography (MEG) recordings to study “working memory,” maintenance of information in mind over brief periods of time. Their results show that the human brain maintains working memory content in transient functional connectivity patterns across sensory and association areas.